Characteristics and early outcomes of cervical cancer patients at Butaro District Hospital, Rwanda: a retrospective review. (April 2017) - Davey, Sonya; Mpanumusingo, Egide; Fehr, Alex; Butonzi, John; Shyireambere, Cyprien; Hategekimana, Vedaste; Bigirimana, Jean Bosco; Borg, Ryan; Uwizeye, Regis; Tapela, Neo; Randall, Tom; Shulman, Lawrence; et al.
Abstract: Background: Cancer treatment facilities are scarce in rural areas of low-income and middle-income countries, where the highest burden of cervical cancer exists. The Butaro Cancer Center of Excellence (BCCOE), in rural Rwanda, is a Rwandan Ministry of Health facility supported by Partners In Health and Dana-Farber/Brigham and Women's Cancer Center. The cervical cancer programme includes diagnosis, staging, and treatment. However, because of resource limitations, only 15 patients per month could be referred for radiotherapy to the Uganda Cancer Institute. In this study, we describe cervical cancer treatment at BCCOE and early patient outcomes. Methods: In July, 2016, we retrospectively reviewed records for patients with cervical cancer enrolled between July 1, 2012, and June 30, 2015, at BCCOE. We extracted data on patients' characteristics, disease stage, treatment, and outcomes. Findings: We included 438 patients: median age was 52 years (IQR 42–60 years), 35 patients (8%) had laboratory-confirmed HIV, 142 (36%) smoked tobacco, median number of pregnancies was 7 (IQR 5–9), and 41 (10%) had had a hysterectomy before enrolment. 258 patients (60%) had a diagnosis confirmed by pathology, and 391 patients (91%) had a documented disease stage. Of these, 13 (3%) were Stage I, 183 (47%) were Stage II, 154 (39%) were Stage-III, and 41 (11%) were Stage IV. There was a curative, instead of palliative or undecided, intent for 85% of Stage I patients, 91% of Stage II, and, 12% of Stage III. 165 women (38%) were referred for concurrent radiation therapy, chemotherapy, and brachytherapy in Uganda, and 19 (4%) were referred for radical hysterectomy. At their last recorded visit, 77 patients (18%) had no evidence of recurrence, including: 6 (46%) Stage I patients, 66 (37%) Stage II, 5 (3%) Stage III, but no Stage IV patients (p =<0·0001). Overall, 114 patients (27%) were lost to follow-up during or after treatment. Interpretation: Our experience shows that a cervical cancer treatment programme is viable in a low-resource, rural setting. However, many challenges exist, especially the severity of disease at intake (about half of patients presented with Stage III or IV disease) and that there are no radiation facilities in Rwanda. Further, a quarter of patients were eventually lost to follow-up during the study. Future implementation interventions will focus on strategies to overcome these challenges. Funding: Partners in Health, Dana-Farber Cancer Institute, Rwandan Ministry of Health.